Effect of electro-acupuncture analgesia on the transport of tryptophan and tyrosine from plasma into brain - Zhang Zhen-de; Liu Xue-jun; Jin Guo-zhang (Acta Pharmacologica Sinica; Vol 1, No 2 (December 1980): Acta Pharmacologica Sinica, 2016)
In rats the effect of electroacupunture analgesia and the levels of tryptophan and tyrosine in plasma and brain were determined.The tryptophan in plasma and brain were increased markedly during acupuncture analgesia. But there was no obvious change in tyrosine transport from plasma into brain. Hence the increment of plasma tryptophan induced by acupncuture had no effect on transport of tyrosine from plasma into brain.